Effect of Water Immersion of Semi-Finished Products on The Fat Content in Fried Potato Products (Agricultural Engineering, 2017)
In this study the influence of selected factors, such as duration of water sorption resulting from the process of reducing sugars elution from semi-finished products, temperature of sorbed water, frying temperature and size of the studied objects (thickness of slices), on the total fat content in dry mass of the obtained products was analyzed. The study was conducted on Innovator cultivar. The scope of the study encompassed 5, 10, 15, 20 min water sorption linked to the process of reducing sugars elution. A control study was also conducted on samples without the process of reducing sugars elution. Temperature of sorbed water was 20 and 40°C; temperature of slice frying was 140 and 180°C; the size of the studied objects, in the experiment limited by the thickness of slices, was 4 and 9 mm. Determination of the total fat content in the products was conducted using the Soxhlet method. The greatest amount of fat in dry weight was contained in the products from samples in which sugars were not eluted, when the process was conducted for a short period of time (several minutes) or when elution continued for the longest period of time, approx. 20 min. The smallest amount of fat was contained in the products from samples in which the immersion in water was conducted for 10-15 min. Thicker slices absorb smaller amounts of fat. Increase of temperature of sorbed water in the process of extracting sugars from semi-finished products results in the increase of the total fat content in dry weight of products.